The art of painting in acrylic - Call, Alicia VanNoy (Collector's series (Walter Foster (Firm)), 2014)
"From beautiful landscapes and seascapes to lifelike animals and compelling still lifes, 'The Art of Painting in Acrylic' features a vast array of easy-to-follow, step-by-step painting lessons from talented professional artist. With inspiration, instruction, and expert tips and tricks on virtually every page, 'The Art of Painting in Acrylic' is your all-inclusive resource and guide to mastering this versatile medium. Dive in and get started on your acrylic painting journey, and discover just how easy painting in acrylic can be!"--Back cover.